Solve for x. -5(3x + 6) = -3(4x - 2) You must show your work.
2 answers:
Answer:
-5(3x + 6) = -3(4x - 2)
Distribute -5 through the parenthesis
-15x - 30 = -3(4x - 2)
distribute -3 through the other parenthesis
-15x - 30 = -3( -12x + 6 )
move the variable the left hand side, change sign
-15x + 12 - 30 = 6
move constant to the right hand side
-15x + 12 = 6 + 30
collect like terms
-3x = 6 + 30
add the numbers
-3x = 36
divide both sides by -3
-3/-3 = 36/-3
x = -12
Answer:
-5(3x + 6) = -3(4x - 2)
-15x-30=-12x+6
-30-6=-12x+15x
3x=-36
x=-36/3=-12
You might be interested in
Answer:
Step-by-step explanation:
(4+1)/(8-2)= 5/6
y + 1 = 5/6(x - 2)
y + 1 = 5/6x - 5/3
y + 3/3 = 5/6x - 5/3
y = 5/6x - 8/3
6(y = 5/6x - 8/3)
6y = 5x - 16
-5x + 6y = -16
Answer:
T=5
Step-by-step explanation:
5 -3 = 10/t
2 =10/t
2t = 10
T = 5
Answer:
8.4 * 10^6
Step-by-step explanation:
8.4 * 10^6
1 million = 1 * 10^6
8 million 4 hundred thousand is 8.4 * 10^4 because this number is 8.4 times bigger than a million.
No, the graph will never reach the x axis because it is an exponential equation, and y = 0 (the x axis) is an undefined asymptote.
V=4/3πr^3, so substitute what you know. Input the volume so you only have to solve one variable, the r, radius.